TRANSFORMING A PLOT OF THE GOSPEL IN PLAYS “ON THE FIELD OF BLOOD” BY LESIA UKRAIINKA AND “GOLGOTHA – HOLY PASSIONS, DEATH AND RESURRECTION OF OUR LORD JESUS CHRIST” BY HRYHOR LUZHNYTSKYI - Vivcharyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article has analyzed the literary devices of dramas “On the Field of Blood” and “Golgotha – Holy Passions, Death, and Resurrection of Our Lord Jesus Christ”. It is proved that both literary works have their origins in mysteries. The author specifies that receptions of the Gospel’s plots or characters depend on the historical epoch, the worldview of the writer, the literary conception, and the genre specificity of the literary work. Hryhir Luzhnytskyi used the method of “revival” of the Biblical story. Lesia Ukraiinka described the terrestrial way of Christ through the retrospective memories of Judas Iscariot, who had sold the Savior for the thirty pieces of silver. The author has also revealed and analyzed the differences between the two variants of play “On the Field of Blood” by Lesia Ukraiinka. She thoroughly described the character of Judas, motivations for his actions, symbolic characters, and details.